On AunAt clusters as potential astatine carriers. Issue 57 (20th July 2017) - Ostrowski, Sławomir; Majkowska-Pilip, Agnieszka; Bilewicz, Aleksander; Dobrowolski, Jan Cz.
Abstract : To understand interactions between astatine atoms with gold clusters the Au n At and Au n X clusters, n = 12 or 13, X = F, Cl, Br, and I, were calculated at the DFT level using basis sets with a quasi-relativistic pseudopotential. Abstract : To understand interactions between astatine atoms with gold clusters the Au n At and Au n X clusters, n = 12 or 13, X = F, Cl, Br, and I, were calculated at the DFT level using basis sets with a quasi-relativistic pseudopotential and the D3 Grimme correction for the dispersion interactions. Among the studied clusters of various geometries, the interaction energy of At to the clusters is the smallest. Yet, consideration of the electron detachment from the X − anion and generation of a H2 molecule and OH − anion from water shows that the formation of the astatine gold clusters is favored.